A new species of Rhododendron (Ericaceae) from Shangri-La, NW Yunnan, China - Liao, Rongli; Xue, Dan; Neilsen, Jens; Wang, Jihua; Ma, Yongpeng (Phytotaxa, 2015)
Rhododendron Linnaeus (1753: 392) exhibits great diversity and roughly 1,025 species are prized in the temperate parts of the world for their horticultural value (Chamberlain et al. 1996). There are approximately 680 species in six subgenera in China, of which more than 400 are endemic (Fang & Min 1995). However, the number of Rhododendron species known is increasing, with many new species being described after the publishing of Flora of China (Fang et al. 2005, Chen et al. 2012, Mao et al. 2013, Ma et al. 2015, Mao & Bhaumik 2015).